Marriage customs in Ilokos and in the United States a contrastive analysis - Espejo, Herminia Averia 1913- (Quezon City College of Education, University of the Philippines Diliman, 1971)
The culture on the marriage customs in Ilokos and in the United States were compared in this study. It begins with a description of the family system and of the child-rearing practices of each culture, then the customs relating to acquaintanceship, to courtship, and to engagement, and the wedding practices of each culture. The customs and practices of the two cultures were contrasted, cross-cultural misinterpretations discussed, and finally, educational implications of the study of the two cultures were explained.
Thesis (Master of Arts in Teaching (English))--University of the Philippines.
Keywords: Marriage customs and rites -- Philippines -- Ilocos Region; Marriage customs and rites -- United States